Apatite powder synthesis method using laser
The laser irradiation of a substrate in an apatite-forming precursor solution synthesizes apatite powder efficiently addresses the limitations of existing methods by providing a cost-effective and efficient method for industrial production.
Patent Information
- Application Number
- CN202110148783.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2021-02-03
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-02-03
AI Technical Summary
Existing methods for synthesizing apatite powder, such as solid phase reaction and hydrothermal synthesis, are inefficient and complex, requiring high temperatures and multiple steps, making them unsuitable for industrial production.
A method involving immersion of a substrate in an apatite-forming precursor solution followed by laser irradiation to synthesize apatite powder, allowing control over particle size, composition, and crystallinity through adjustments in laser parameters and precursor solution concentration.
Facilitates the production of apatite powder with controlled properties, enabling efficient and versatile manufacturing of various shapes and sizes without the need for high-temperature treatments, thus improving industrial applicability.
Smart Images

Figure CN113548652B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for synthesizing apatite powder using laser, and in particular to a method for forming apatite powder by immersing a substrate in a precursor solution for forming apatite and irradiating the substrate with laser. Background Art
[0002] As the most widely used medical metal material, titanium-based alloy has low elastic modulus and outstanding biocompatibility, and its corrosion resistance is better than that of previously used biometals. However, due to its biological inertness, it cannot directly induce bone formation, and a considerable treatment time is required to achieve bone bonding. In addition, the thickness of the naturally formed oxide powder is thin and disappears quickly, making it impossible to guide the regeneration of adjacent bone tissue.
[0003] Therefore, implant surface treatment is being used to impart bioactivity to solve the above-mentioned problem that implants cannot directly integrate with bones and solve the problem of looseness in order to shorten the bone integration period. The surface of titanium, which is the main material of implants, is being treated by physical and chemical methods to further improve bioactivity, thereby shortening the healing period after implants are placed in the human body, and research on more effective surface treatment is being continuously conducted.
[0004] At this time, hydroxyapatite is used as a material for surface treatment of titanium. As a basic component of hard tissues in the human body, hydroxyapatite is also used as a bone tissue transplant or bone regeneration material. The chemical structure of hydroxyapatite is Ca 10 (PO4)6(OH)2, hydroxyapatite in human tooth enamel is mainly distributed in the outermost layer of tooth enamel with a thickness of about 1 to 2 mm. This hydroxyapatite can show a remineralization effect, and therefore has the function of filling the tiny gaps in decalcified tooth enamel.
[0005] In addition to the above-mentioned implant surface treatment, apatite is also required to have suitable particle components and particle sizes according to different application fields to provide characteristics corresponding to the use. In the past, solid phase reaction method and hydrothermal synthesis method were mainly used to prepare needle-shaped or plate-shaped apatite particles. However, these existing methods have many problems.
[0006] The problem with the solid phase reaction method is that the heat treatment temperature is a high temperature of about 800°C to 1200°C, so the prepared particles will increase to tens of microns, and after the reaction, complex post-processing steps such as mixing, calcination, and crushing are required. Therefore, it cannot be an industrially advantageous method.
[0007] On the other hand, the hydrothermal synthesis method is generally a method of using amorphous precipitated calcium phosphate to react in an autoclave at a temperature range of about 150 to 250°C. It requires two steps of precipitation and hydrothermal synthesis, and requires mixing of multiple additives. The process itself is complicated, and therefore, there are problems in mass production. Summary of the invention
[0008] Technical issues
[0009] The present invention aims to solve the above-mentioned problems and has an object to provide a method for synthesizing apatite powder using laser, wherein the method comprises irradiating the surface of a substrate immersed in an apatite-forming precursor solution with laser light to synthesize apatite powder.
[0010] However, this technical problem is exemplary, and the scope of the present invention is not limited thereto.
[0011] Technical Solution
[0012] According to one aspect of the present invention for achieving the above-mentioned purpose, a method for synthesizing apatite powder using laser is provided, which comprises the following steps: (a) immersing a substrate in a precursor solution for forming apatite; (b) irradiating a region on the substrate immersed in the precursor solution for forming apatite with a laser beam; and (c) obtaining apatite powder generated in the precursor solution for forming apatite.
[0013] In addition, according to an embodiment of the present invention, the apatite powder represented by Chemical Formula 1 can be synthesized in the step (c).
[0014] Chemical formula 1:
[0015] (M1) a (M2) 10-a (ZO4)6(X)2
[0016] Wherein, M1 and M2 are selected from Ca 2+ , Pb 2+ , Sr 2+ Mg 2+ , Fe 2+ , Mn 2+ 、Cd 2+ , Ba 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Sn 2+ 、Eu 2+ 、Na + , K + , Li + , Rb + NH4+ ,La 3+ 、Ce 3+ 、Sm 3+ 、Eu 3+ , Y 3+ 、Bi 3+ Cr 3+ ,Th 4+ , U 4+ and U 6+ One of
[0017] ZO4 is selected from PO4 3- 、AsO4 3- 、SiO4 4- , VO4 3- 、CrO4 3- 、CrO4 2- 、MnO4 3- 、SO4 2- 、SeO4 2- 、BeF4 2- 、GeO4 4- 、ReO5 3- 、SbO3F 4- 、SiON 5- , BO4 5- , BO3 3- and CO3 2- One of
[0018] X is selected from F - OH - , Cl - 、O2 - 、O3 - 、NCO - , BO2 - Br - ,I - 、NO2 - 、NO3 - 、CO3 2- 、O2 2- , O 2- , S 2- 、NCN 2- and NO2 2- One of
[0019] a is a real number between 0 and 10.
[0020] In addition, according to an embodiment of the present invention, in the step (a), M1 ions, M2 ions and ZO4 ions may be dissolved in the apatite-forming precursor solution.
[0021] In addition, according to one embodiment of the present invention, when the apatite-forming precursor solution contains Ca 2+ Ions and PO4 3- ions, hydroxyapatite powder can be formed in the step (c).
[0022] In addition, according to one embodiment of the present invention, when the apatite-forming precursor solution contains Mg 2+ When ions are present, an apatite powder selected from the group consisting of hydroxyapatite, Mg-containing apatite, whitlockite and a combination thereof can be formed in the step (c).
[0023] In addition, according to an embodiment of the present invention, the size of the apatite powder may be controlled by adjusting the concentration of the apatite-forming precursor solution.
[0024] In addition, according to an embodiment of the present invention, the step (b) may include a step of adjusting the laser beam irradiation time to control the size of the generated apatite powder.
[0025] In addition, according to an embodiment of the present invention, the step (b) may include the step of adjusting the output power of the laser beam to control the size of the generated apatite powder.
[0026] In addition, according to one embodiment of the present invention, the composition of the apatite powder can be controlled by adjusting the composition of the apatite-forming precursor solution. In addition, according to one embodiment of the present invention, the (M1+M2) / ZO4 ratio of the apatite powder can be controlled by adjusting the concentration of the apatite-forming precursor solution.
[0027] In addition, according to an embodiment of the present invention, the crystallinity of the apatite powder can be controlled by adjusting the power of the laser beam.
[0028] In addition, according to an embodiment of the present invention, the crystallinity of the apatite powder can be controlled by adjusting the pulse width of the laser beam.
[0029] Beneficial Effects
[0030] According to one embodiment of the present invention described above, there is an effect that a surface of a substrate immersed in an apatite-forming precursor solution can be irradiated with laser light to synthesize apatite powder having adjusted composition and size.
[0031] However, the above-mentioned problems are merely examples, and the scope of the present invention is not limited thereto. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 1 is a SEM image of apatite powder formed by laser power according to an embodiment, and a graph showing the size of the formed apatite powder as a function of laser power.
[0033] Figure 2 FIG. 1 is a graph showing the size of apatite formed according to the concentration of an apatite-forming precursor solution and the laser irradiation time according to one embodiment.
[0034] Figure 3 is a SEM image of whitlockite crystals generated according to one embodiment.
[0035] Figure 4 1 and 2 are SEM images of apatite crystals generated according to an embodiment and a comparative example.
[0036] Figure 5 Graphs showing the size and growth rate of apatite crystals produced according to an example and a comparative example.
[0037] Figure 6 1 is a SEM image of Mg-containing apatite crystals generated according to an embodiment and a Mg content analysis result.
[0038] Figures 7 to 9 The electron microscope and XRD measurement results of apatite in one embodiment are shown.
[0039] Fig.10 is an EDS measurement result after apatite is generated according to an embodiment.
[0040] Fig.11 1 is the XRD and electron microscope measurement results of the apatite powder synthesized by adjusting the laser power in one embodiment.
[0041] Fig.12 1 is the XRD and electron microscope measurement results of the apatite powder synthesized by adjusting the laser pulse width in one embodiment. DETAILED DESCRIPTION
[0042] The detailed description of the invention described below will refer to the accompanying drawings, which will show specific embodiments that can implement the invention as examples. These embodiments are fully described so that those skilled in the art can implement the invention. It should be understood that the multiple embodiments of the present invention are different from each other but not necessarily mutually exclusive. For example, the specific shapes, structures and characteristics recorded here are associated with one embodiment and can be implemented as other embodiments without departing from the spirit and scope of the present invention. In addition, it should be understood that the position or configuration of each constituent element within each disclosed embodiment can be changed without departing from the spirit and scope of the present invention. Therefore, the detailed description described below is not restrictive, and as long as it is properly described, the scope of the present invention is limited only by its claims and their equivalents. Similar figure numbers in the drawings refer to the same or similar functions in various aspects, and for convenience, exaggerated expressions can be made.
[0043] Hereinafter, several preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention.
[0044] A method for synthesizing apatite powder according to one embodiment of the present invention comprises the following steps: (a) immersing a substrate in an apatite-forming precursor solution; (b) irradiating a region on the substrate immersed in the apatite-forming precursor solution with a laser beam; and (c) obtaining apatite powder generated in the apatite-forming precursor solution.
[0045] The substrate as a material for forming an apatite film on the surface may be, for example, a biometal. For example, the substrate may be any one selected from titanium, titanium alloy, magnesium and magnesium alloy. In addition, as a metal material or a ceramic material, a material required to form an apatite film may be used.
[0046] The present invention forms apatite powder containing ions contained in the apatite-forming precursor solution by laser irradiation, and therefore, the type of ions contained in the apatite-forming precursor solution is not particularly limited. In one embodiment, as a solution for supplying a raw material for generating apatite, the apatite-forming precursor solution may contain a material selected from Ca 2+ , Pb 2+ , Sr 2+ Mg 2+ , Fe 2+ , Mn 2+ 、Cd 2+ , Ba 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Sn 2+ 、Eu 2+ 、Na + , K + , Li + , Rb + NH4 + ,La 3 + 、Ce 3+ 、Sm 3+ 、Eu 3+ , Y 3+ 、Bi 3+ Cr 3+ ,Th 4+ , U 4+ and U 6+ The cations in the PO4 3- 、AsO4 3- 、SiO4 4- , VO4 3-、CrO4 3- 、CrO4 2- 、MnO4 3- 、SO4 2- 、SeO4 2- 、BeF4 2- 、GeO4 4- 、ReO5 3- 、SbO3F 4- 、SiON 5- , BO4 5- , BO3 3- and CO3 2- Additionally, it may further comprise an anion selected from F - OH - , Cl - 、O2 - 、O3 - 、NCO - , BO2 - Br - ,I - 、NO2 - 、NO3 - 、CO3 2- 、O2 2- , O 2- , S 2- 、NCN 2- and NO2 2- When the apatite-forming precursor solution containing the above ions is used, the apatite powder represented by Chemical Formula 1 can be synthesized in the apatite-forming precursor solution.
[0047] Chemical formula 1:
[0048] (M1) a (M2) 10-a (ZO4)6(X)2
[0049] Wherein, M1 and M2 are selected from Ca 2+ , Pb 2+ , Sr 2+ Mg 2+ , Fe 2+ , Mn 2+ 、Cd 2+ , Ba 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Sn 2+ 、Eu 2+ 、Na + , K + , Li + , Rb+ NH4 + ,La 3+ 、Ce 3+ 、Sm 3+ 、Eu 3+ , Y 3+ 、Bi 3+ Cr 3+ ,Th 4+ , U 4+ and U 6+ One of the above, ZO4 is selected from PO4 3- 、AsO4 3- 、SiO4 4- , VO4 3- 、CrO4 3- 、CrO4 2- 、MnO4 3- 、SO4 2- 、SeO4 2- 、BeF4 2- 、GeO4 4- 、ReO5 3- 、SbO3F 4- 、SiON 5- , BO4 5- , BO3 3- and CO3 2- One of the following, X is selected from F - OH - , Cl - 、O2 - 、O3 - 、NCO - , BO2 - Br - ,I - 、NO2 - 、NO3 - 、CO3 2- 、O2 2- , O 2- , S 2- 、NCN 2- and NO2 2- One of: a is a real number between 0 and 10. That is, the apatite powder containing the ions dissolved in the apatite-forming precursor solution can be formed in the solution by laser irradiation.
[0050] As an example of a precursor solution for producing apatite, a solution containing Ca 2+ Ions and PO4 3- For example, a precursor solution containing Ca 2+ Ions and PO4 3-The precursor solution of ions may be selected from a solution containing an inorganic component including DMEM (Dulbecco Modified Eagle Medium), HBSS (Hank's Balanced Salt Solution), HBP (Human blood plasma), and SBF (Simulated body fluid). The Ca content of the apatite-forming precursor solution may be 2+ Ions and PO4 3- The concentration of the ions is increased by 1 to 400 times before use to promote the formation of apatite. However, the present invention is not limited thereto, as long as the concentration of the precursor solution can be adjusted according to the purpose of synthesis.
[0051] When a high-energy laser beam is irradiated onto the surface of a substrate immersed in an apatite-forming precursor solution, the Ca in the precursor solution can be 2+ Ions and PO4 3- The ions are activated by reaction to form apatite powder. Subsequently, the generated apatite powder can be separated from the solution and solidified to form a molded body.
[0052] In the past, apatite powder was synthesized by solid phase synthesis, liquid phase synthesis, gas phase synthesis, hydrothermal synthesis and other methods. The problem with the existing methods is that the process is complicated and requires high temperature heat treatment. Different from this, according to an embodiment of the present invention, a laser beam can be irradiated to a region on a substrate in a precursor solution to form an apatite film on the substrate and apatite powder is formed in the solution at the same time. The apatite powder thus generated can be separated and dried, and products of various shapes can be manufactured by subsequent molding. Therefore, the utilization rate is higher than when it is formed into a coating.
[0053] As an energy supply source for supplying energy for forming apatite, a laser generator can be used, for example, a Ytterbium Nanosecond Pulsed laser generator or a femtosecond laser generator. In this case, nanosecond laser means a laser with a pulse time of several nanoseconds and a power of 10 -9 Femtosecond laser refers to a laser with a pulse width of 10 -15 However, the present invention is not limited thereto, and any laser can be used as long as it can apply sufficient energy to the precursor solution to generate apatite.
[0054] The size of the generated apatite powder can be changed by controlling the concentration of the apatite-forming precursor solution and the conditions of the laser beam, for example, the power of the laser beam, the irradiation time, and the like.
[0055] The composition and concentration of the apatite-forming precursor solution can be adjusted to change the composition of the apatite powder. For example, when the apatite-forming precursor solution contains Mg 2+ ions, can be based on Mg 2+ The content of ions can be adjusted to form any apatite powder selected from hydroxyapatite, Mg-containing apatite, whitlockite, and combinations thereof. As another example, the (M1+M2) / ZO4 ratio of the apatite powder can be controlled by adjusting the concentration of the apatite-forming precursor solution.
[0056] According to an embodiment of the present invention, the crystallinity of the apatite powder can be adjusted by controlling the laser beam irradiation conditions, for example, the laser power, pulse width, wavelength, pulse energy, repetition rate, irradiation time, etc.
[0057] Hereinafter, a plurality of embodiments are described, and the embodiments are used to help understand the present invention. However, the following embodiments are only used to help understand the present invention, and the present invention is not limited to the following embodiments.
[0058] Example
[0059] Titanium or magnesium is used as the substrate. DMEM with a concentration increased by 100 to 400 times is added to the precursor solution impregnation part located on the upper part of the PDMS template fixed with the substrate. Then, a laser beam is irradiated to the surface of the substrate using a Ytterbium nanosecond pulsed fiber laser to form apatite powder. The power of the laser beam is selected from the range of 1W to 15W, and the irradiation time is selected from the range of 15 minutes to 30 minutes.
[0060] Experimental example
[0061] Figure 1 The results of analyzing the size of apatite powder synthesized according to the laser power show that the size of the synthesized powder is about 50nm to 6000nm when the power is 1W to 15W. It can be confirmed that the higher the laser irradiation energy, the larger the size of the generated apatite powder.
[0062] Figure 2 : is a graph showing the size of apatite formed according to the concentration of apatite-forming precursor solution and the laser irradiation time. It can be confirmed that the higher the concentration of the precursor solution and the longer the laser irradiation time, the larger the size of the apatite powder formed. When the laser is irradiated on the magnesium substrate, the size of the apatite powder formed is smaller than that on the titanium substrate. Therefore, it can be expected that even if the laser of the same energy is irradiated, the degree of temperature rise will be different depending on the substrate.
[0063] Figure 3 This is a SEM image of whitlockite crystals generated from an apatite-forming precursor solution containing Mg ions. This confirms that apatite crystals were generated by laser.
[0064] Figure 4 and Figure 5 : is a figure which shows the image and crystal size of the apatite crystal produced|generated according to one Example and a comparative example. Figure 4 (a) and (b) are electron microscope images of crystals formed by hydrothermal synthesis of whitlockite and crystals grown for two weeks (reference: Jang, Hae Lin, et al. "Phase transformation from hydroxyapatite to the secondary bone mineral, whitlockite." Journal of Materials Chemistry B 3.7 (2015): 1342-1349), wherein the whitlockite is apatite containing Mg ions. Figure 4 (c) is an electron microscope image of a crystal formed by synthesizing whitlockite by laser irradiation, wherein whitlockite is apatite containing Mg ions.
[0065] exist Figure 5 In (a), the size of the whitlockite crystal synthesized by hydrothermal synthesis is about 87nm, and the size after two weeks of growth is about 212nm. However, the size of the whitlockite crystal synthesized by laser in 15 minutes is about 1759nm, which means that crystals with a minimum size of about 8 times and a maximum size of 20 times can be formed. Figure 5 (b) shows the "crystal growth rate (growth rate)" obtained by dividing the crystal size by the reaction time. The method using laser has a crystal growth rate that is about 11147 times faster than the crystal growth rate using the hydrothermal synthesis method.
[0066] Figure 6 The following are SEM images of the generated Mg-containing apatite crystals and the results of Mg content analysis. This indicates that the composition of the synthesized powder can be adjusted by adjusting the ion composition of the reaction solution.
[0067] Figure 7 and Figure 8The electron microscope and XRD measurement results of the apatite of the embodiment. As the phase analysis results of the powder synthesized by changing the pulse width and power of the laser, a pure hydroxyapatite phase was observed under all laser conditions. This means that even if the laser conditions (pulse width, power) are changed, the powder can be synthesized stably without phase change.
[0068] Fig. 9 It is shown that pure hydroxyapatite, apatite containing a Mg component, and powders having a whitlockite phase can be synthesized by adjusting the components of the precursor solution.
[0069] Fig.10 : is the result of EDS measurement after apatite is generated according to the example. : shows the ratio of Ca to P content of the synthesized powder when the apatite-forming precursor solution with adjusted composition is used to synthesize the powder, indicating that the powder with adjusted Ca / P ratio can be synthesized.
[0070] Fig.11 3 is a result showing the change in crystallinity of the synthesized powder according to the laser power when synthesizing apatite powder using laser. Fig.11 (a) is the XRD measurement result of apatite powder. The higher the crystallinity, the thinner the peak thickness and the higher the height. When the laser power is 1W, it shows a relatively high crystallinity. Fig.11 (b) is the result of observing apatite powder using SEM, TEM, and TEM-SAD. The higher the crystallinity, the more white dots appear in TEM-SAD, and when the laser power is 1W, a relatively high crystallinity is shown.
[0071] Fig.12 2 is a result showing the change in crystallinity of the synthesized powder according to the laser pulse width when synthesizing apatite powder using laser. Fig.12 , when the pulse width of the laser is 4ns, the crystallinity is relatively high, and when it is 200ns, the crystallinity is relatively low.
[0072] Summarize Fig.11 as well as Fig.12 As a result, the power and pulse width of the laser can be changed to adjust the crystallinity of the synthesized apatite powder.
[0073] In summary, according to the embodiments of the present invention, apatite powder particles can be formed while forming an apatite film, so the powder preparation method is simple, and products of various sizes and shapes can be manufactured through subsequent powder molding, so the utilization rate is high.
[0074] The present invention has been described using a number of preferred embodiments, but the present invention is not limited to the embodiments, and those skilled in the art can make various modifications and changes without departing from the spirit of the present invention. These modifications and changes should be considered to be within the scope of the present invention and the appended claims.
Claims
1. A method for synthesizing apatite powder using laser, comprising the following steps: (a) immersing a substrate in an apatite-forming precursor solution; (b) irradiating a region on the substrate immersed in the apatite-forming precursor solution with a laser beam; and (c) separating the apatite powder generated in the apatite-forming precursor solution from the apatite-forming precursor solution to obtain the apatite powder, in, The substrate is made of any one selected from titanium, titanium alloy, magnesium and magnesium alloy. In the step (c), an apatite powder represented by Chemical Formula 1 is synthesized, Chemical formula 1: (M1) a (M2) 10-a (ZO4)6(X)2 Wherein, M1 and M2 are selected from Ca 2+ Mg 2+ One of ZO4 is PO4 3- , X is selected from F - OH - , Cl - 、O2 - 、O3 - 、NCO - , BO2 - Br - ,I - 、NO2 - 、NO3 - 、CO3 2- 、O2 2- , O 2- , S 2- 、NCN 2- and NO2 2- One of a is a real number between 0 and 10, In the step (a), M1 ions, M2 ions and ZO4 ions are dissolved in the apatite-forming precursor solution.
2. The method for synthesizing apatite powder using laser according to claim 1, wherein: When the apatite-forming precursor solution contains Ca 2+ Ions and PO4 3- ions, hydroxyapatite powder is formed in the step (c).
3. The method for synthesizing apatite powder using laser according to claim 1, wherein: When the apatite-forming precursor solution contains Mg 2+ ions, an apatite powder selected from the group consisting of hydroxyapatite, Mg-containing apatite, white apatite and a combination thereof is formed in the step (c).
4. The method for synthesizing apatite powder using laser according to claim 1, wherein: The size of the apatite powder is controlled by adjusting the concentration of the apatite-forming precursor solution.
5. The method for synthesizing apatite powder using laser according to claim 1, wherein: The step (b) includes adjusting the laser beam irradiation time to control the size of the generated apatite powder.
6. The method for synthesizing apatite powder using laser according to claim 1, wherein: The step (b) includes adjusting the output power of the laser beam to control the size of the generated apatite powder.
7. The method for synthesizing apatite powder using laser according to claim 1, wherein: The composition of the apatite powder is controlled by adjusting the composition of the apatite-forming precursor solution.
8. The method for synthesizing apatite powder using laser according to claim 1, wherein: The (M1+M2) / ZO4 ratio of the apatite powder is controlled by adjusting the concentration of the apatite-forming precursor solution.
9. The method for synthesizing apatite powder using laser according to claim 1, wherein: The crystallinity of the apatite powder is controlled by adjusting the power of the laser beam.
10. The method for synthesizing apatite powder using laser according to claim 1, wherein: The crystallinity of the apatite powder is controlled by adjusting the pulse width of the laser beam.